1979
DOI: 10.1111/j.1600-0773.1979.tb02378.x
|View full text |Cite
|
Sign up to set email alerts
|

Dextran‐induced Lowering of Parameters of the Kallikrein‐kinin System in Rat Plasma: Significance of Monoamine‐depleting Agents

Abstract: Significant reductions were registered in the plasma levels of prekallikrein proactivator (pro‐PKA), prekallikrein (PK), and high molecular weight kininogen (HMWK) 3‐5 min. after the intravenous injection into rats of serotonin (0.02‐0.20 mg/kg) or noradrenaline (0.02 mg/kg), whereas adrenaline (0.02 mg/kg) showed no effect, and tyramine (3.0 mg/kg) only slightly lowered the parameters mentioned. Pretreatment with reserpine (1.5 mg/kg) injected intraperitoneally 24 hours before dextran (10 mg/100 g) inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
20
0

Year Published

1979
1979
1982
1982

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(28 citation statements)
references
References 9 publications
8
20
0
Order By: Relevance
“…The BAEe-esterase activity developed by activation of RCPL with acetone and kaolin was found to be somewhat higher that that registered for RCPL-P (Briseid et al 1978b;Briseid & Berstad 1979). Gel filtration experiments in the present work suggested that such a higher activity in RCPL is due to the presence of an additional BAEe-esterase with a molecular weight of about 47,000 (K 2, fig.…”
Section: Baee-esterase In Acetone-and Kaolin-activated Rcpl and Rcpl-pmentioning
confidence: 69%
See 2 more Smart Citations
“…The BAEe-esterase activity developed by activation of RCPL with acetone and kaolin was found to be somewhat higher that that registered for RCPL-P (Briseid et al 1978b;Briseid & Berstad 1979). Gel filtration experiments in the present work suggested that such a higher activity in RCPL is due to the presence of an additional BAEe-esterase with a molecular weight of about 47,000 (K 2, fig.…”
Section: Baee-esterase In Acetone-and Kaolin-activated Rcpl and Rcpl-pmentioning
confidence: 69%
“…1973), because kallikreiri was present in a high concentration in the preparation. It should also be emphasized that the factor in question does not seem to be identical with by Briseid et al (1978b) to be only slightly lowered by the passage of RCPL through a column of I ysine-Sepharose.…”
Section: Prekallikrein Activator In Acetone-and Kaolin-activated Rcplmentioning
confidence: 99%
See 1 more Smart Citation
“…The observed lowering by dextran of plasminogen proactivator, pro-PGA, (Berstad & Briseid 1982) was accordingly to be expected. More surprising, however, was the fact that EACA or AMCHA did not cause any detectable inhibition of the lowering of PG caused by dextran (Briseid et al 1979) or serotonin (Berstad 1980a), nor did recent in vitro experiments reveal an inhibition by AMCHA of the PGA activity developed by acetone treatment of rat plasma (Berstad & Briseid 1982). On the other hand, AMCHA alone was found to cause a clear lowering of the capacity ofHMWK to function as a cofactor in the activation of factor XI1 (Briseid et a/.…”
Section: Discussionmentioning
confidence: 96%
“…Dextran injected intravenously into rats was previously found to cause some reduction of the level of plasminogen (PG) in plasma (Briseid et a/. 1979;Berstad 1980a), an effect probably mediated through a release of serotonin from mast cells (Berstad 1980a & b).…”
Section: Discussionmentioning
confidence: 99%